Efikasi Bakterostatik Kulit Bawang Merah Pada Ikan Bandeng (Chanos chanos) Selama Penyimpanan Suhu Ruang - Asha, Nur Aisha; Syukroni, Ikbal; Tasir, Tasir (Jambura Fish Processing Journal, 2024)
Biochemical and physicochemical changes result in a decrease in fish freshness. The decline in quality of fresh fish can be influenced by several things, one of which is storage temperature, where the higher the storage temperature, the faster the fish rots. Red onion skin contains flavonoid compounds which function as bacteriostatics, namely quercetin. The aim of this research is to provide scientific information about the bacteriostatic efficacy of shallot skin on histamine inhibition in milkfish during room temperature storage. The research design used was a Randomized Block Design (RAK) with three treatment factors with two replications. Based on the research results, it was found that it showed the best concentration and had a significant effect on the quality (pH, histamine and TPC) of crushed milkfish during 48 hours of storage at room temperature with the addition of 3% shallot skin. The results of the organoleptic test showed that the red onion skin of crushed milkfish experienced a decrease in organoleptic values for each parameter (Appearance, Smell, Texture) for 48 hours so it was necessary to increase the concentration of red onion skin.